Organic matter in delayed coking wastewater: Molecular composition and its effect on emulsification. (1st November 2020) - He, Chen; Zhong, Heng; Zhang, Yiping; Li, Yuguo; Chung, Keng H.; Fang, Li; Zhang, Weilai; Wu, Baichun; Xu, Chunming; Shi, Quan
Graphical abstract: Highlights: Emulsified wastewater from a delayed coking unit was investigated. Molecular composition of organics in the wastewater was characterized by FT-ICR MS. Highly condensed heteroatoms were dominant in the emulsified wastewater. Sulfonates and polyoxyethylene surfactants were found in the DOM. Abstract: Delayed coking is a common resid conversion process used in refining operations. A large amount of oil-containing wastewater is produced during the hydraulic decoking process. The coking wastewater contains emulsions which are difficult to process in water treatment plants, especially when the coker is fed with feedstocks have high content of heteroatoms. This study examined the molecular composition of emulsified oil and dissolved organic matter (DOM) in coking wastewater. The emulsification agents in coking wastewater were identified. The emulsified oil and DOM were separated and enriched by liquid–liquid extraction, solid phase extraction, and adsorption chromatography, and then characterized by gas chromatography-mass spectrometry and electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry analyses. The results showed that the emulsified oil and DOM in coking wastewater contained highly condensed molecules with a large number of nitrogen and oxygen heteroatomic compounds. The Ox Sy surfactants and their derivatives, polyoxyethylene ether, and the strong polar oxygen-, nitrogen-, and sulfur-containing compounds are likely the oil–water emulsification agents.